Carbon nanotube / layered double hydroxide / cadmium sulfide composite photocatalyst as well as preparation method and application thereof

By loading CoMo-LDH in situ on carbon nanotubes and forming a composite structure with CdS, the problem of electron hole recombination and light absorption range limited in the process of photocatalytic decomposition of aquatic hydrogen is solved, and efficient light is achieved Improved catalytic hydrogen production performance.

CN119259079APending Publication Date: 2025-01-07ZHONGBEI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411262463.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing photocatalysts such as CdS and TiO2 are limited by rapid electron-hole recombination and narrow light absorption range in the process of photocatalytic decomposition of aquatic hydrogen, resulting in poor performance and difficulty in making more efficient photocatalytic materials.

Method used

CoMo-LDH nanocages were prepared by metal ion etching method and formed a composite structure with CdS. CoMo-LDH/CdS was loaded with carbon nanotubes to construct heterojunctions to accelerate electron separation and migration and improve photocatalytic reaction activity.

Benefits of technology

The photocatalytic hydrogen production rate was significantly improved, reaching 46.76 mmol g-1 h-1, exceeding 11 times that of pure CdS, and the charge separation and migration efficiency was enhanced by regulating the energy band structure and morphological design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259079A_ABST
    Figure CN119259079A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nano tube / layered double hydroxide / cadmium sulfide composite photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of hydrogen desorption by photocatalysis of water. The mass fraction of the carbon nano tube in the composite photocatalyst is 0.02%-0.04%, the mass fraction of the layered double metal hydroxide in the composite photocatalyst is 46.96%-51.98%, and the mass fraction of the cadmium sulfide in the composite photocatalyst is 48%-53%. According to the invention, Co-ZIF is anchored on a carbon nanotube by using carboxyl groups on the surface of an acid functionalized carbon nanotube; in the etching process, the surface of the CNT / Co-ZIF is roughened and a layered structure is generated by utilizing ion exchange and hydration reaction, so that the Co-ZIF is converted into CoMo-LDH; after the cocatalyst CNT / CoMo-LDH is compounded with CdS, the cocatalyst CNT / CoMo-LDH not only has good morphology and dispersity, but also accelerates electron transfer and improves the separation and migration efficiency of photo-induced electrons-holes by virtue of the serially connected carbon nanotubes, so that the photocatalytic water decomposition and hydrogen evolution performance of the nano semiconductor CdS is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst and a preparation method and application thereof, belonging to the technical field of photocatalytic water decomposition hydrogen. Background Art

[0002] In recent years, the rapid consumption of global energy and the resulting environmental problems have attracted widespread attention from the society. Hydrogen fuel is a safe, sustainable and environmentally friendly energy source, and water splitting is a promising method for hydrogen fuel production. Generally speaking, photocatalytic water splitting to produce hydrogen includes three main steps: (1) the semiconductor generates electron-hole pairs by absorbing light; (2) charge separation and migration to the semiconductor surface; (3) H2 overflow reaction on the surface. Although many semiconductor materials such as CdS and TiO2 have been reported in the relevant literature (RSC Advances, 2018, 8(21): 11489; Int. J. Hydrogen Energy, 2021, 46: 15389; Chemical Engineering Journal, 2018, 346: 226), they are limited by fast electron-hole recombination or narrow light absorption range and have poor performance. Therefore, it remains a challenge to manufacture more efficient photocatalytic materials.

[0003] The performance of photocatalysts can be improved through strategies such as morphology control, heterostructure construction, element doping, and co-catalyst modification. Among them, the construction of heterojunctions not only enriches the reaction sites, but also accelerates the separation of photogenerated carriers in the space charge region due to the formation of a built-in electric field, thereby enhancing the activity of the photocatalytic reaction, and has been widely studied. Layered double hydroxides (LDH) are widely used as catalysts to promote catalytic performance due to the characteristics of variable interlayer anion elements and adjustable interlayer spacing. Especially for the composite of LDH nanosheets and CdS, the traditional hydrothermal method is often used to prepare LDH nanosheets, which is easy to produce accumulation, reduce the specific surface area, and thus reduce the exposure of active sites. Different from the traditional hydrothermal method for preparing LDH nanosheets, the present invention uses a metal ion etching method to prepare CoMo-LDH nanocages, providing a carbon nanotube / layered double hydroxide / cadmium sulfide composite photocatalyst. Summary of the invention

[0004] The present invention aims to provide a carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst and a preparation method and application thereof. After in-situ loading of CoMo-LDH as a co-catalyst on carbon nanotubes to composite nano CdS semiconductors, a CNT / CoMo-LDH / CdS composite photocatalyst is constructed. By rationally designing the morphology and structure of the catalyst, the electron separation and migration efficiency in the catalyst is accelerated, the recombination of photogenerated carriers is suppressed, and thus the photocatalytic hydrogen production performance of the CdS-based semiconductor is improved.

[0005] The present invention introduces cobalt-molybdenum layered double hydroxide (CoMo-LDH) into the field of photocatalytic hydrogen production, and provides a preparation method and application of a composite photocatalyst of carbon nanotubes (CNT) loaded with CoMo-LDH and CdS, namely CNT / CoMo-LDH / CdS. The present invention adopts a metal ion etching method to prepare CoMo-LDH nanocages, which not only has a hollow cage-like morphology that is conducive to exposing more active sites, but also CoMo-LDH and CdS are in close contact to form a heterojunction, which can accelerate the transfer of photogenerated electrons; in addition, the nanocage structure of CoMo-LDH can also regulate its band structure, so that it maintains a high barrier difference with CdS, further promoting the transfer of photogenerated electrons, thereby enhancing the separation and migration efficiency of charges and improving the rate of photocatalytic hydrogen production.

[0006] The present invention provides a carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst, wherein the mass fractions of the carbon nanotube, the layered double metal hydroxide and the cadmium sulfide in the composite photocatalyst are 0.02%-0.04%, 46.96%-51.98% and 48%-53% respectively.

[0007] The present invention provides a method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst, comprising the following steps: In the first step, through ion exchange and hydration reaction, highly dispersed carbon nanotubes loaded with Co-ZIF (CNT / Co-ZIF) are etched using a molybdenum source, so that the Co-ZIF on the CNT / Co-ZIF evolves into a layered structure CoMo-LDH to obtain CNT / CoMo-LDH; In the second step, CNT / CoMo-LDH is used as a carrier, and a cadmium source, a sulfur source and a sodium hydroxide solution are added to hydrothermally load CdS in situ to obtain a CNT / CoMo-LDH / CdS composite photocatalyst; through reasonable design, CNT is interspersed in the composite material, playing a role similar to a "wire" so that the composite material is connected in series like a "circuit", which accelerates the electron transfer in the composite material. In addition, the present invention successfully introduces CoMo-LDH into the composite material and constructs a heterostructure with CdS. The type II heterojunction formed by the two accelerates the migration and transportation of photogenerated electron-hole pairs, thereby inhibiting the recombination of photogenerated electron-hole pairs and improving the efficiency of photocatalytic hydrogen production.

[0008] The above cobalt source is: any one of cobalt nitrate and cobalt chloride; the molybdenum source is Keggin type phosphomolybdic acid PMo 12 , ammonium molybdate AMT, sodium molybdate; the cadmium source is any one of cadmium chloride, cadmium nitrate, cadmium acetate; the sulfur source is any one of thiourea, sodium sulfide, thioacetamide.

[0009] The method for preparing the composite photocatalyst CNT / CoMo-LDH / CdS of the carbon nanotube-loaded layered double metal hydroxide and CdS comprises the following specific steps: (1) Disperse 1 g of commercial carbon nanotubes in 100 mL of a mixed acid of sulfuric acid and nitric acid in a volume ratio of 3:1, use an ultrasonic instrument with an ultrasonic frequency of 40 kHz for 5 min, and then reflux in a 60°C water bath for 5 h; after the reaction is completed and cooled to room temperature, wash the reactant with water and filter it until the pH is neutral, and freeze-dry to obtain acid-treated CNTs; (2) Dissolve 0.01-0.02 g of the acid-treated carbon nanotubes in 20 mL of anhydrous methanol (or water), add 0.31-0.40 g of a cobalt source, and sonicate for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to form a uniform solution A; (3) Dissolve 0.8-1.0 g of 2-methylimidazole in 20 mL of anhydrous methanol (or water), and sonicate for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to form a uniform solution B (in a complete preparation process, the solvent used in steps 2 and 3 is the same); (4) The solution A in step (2) and the solution B in step (3) are mixed evenly and stirred for 2 h to obtain a composite CNT / Co-ZIF in which Co-ZIF is connected in series by carbon nanotubes; (5) Disperse 0.02-0.04 g of the CNT / Co-ZIF obtained in step (4) in 40 mL of anhydrous ethanol, and sonicate for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to form a uniform solution C; (6) Dissolve 0.006-0.14 g of molybdenum source in 10 mL of water and ultrasonicate for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to form a uniform solution D; (7) The solution C in step (5) and the solution D in step (6) are mixed evenly, and hydrothermal treatment is performed at 80-100° C. for 1.5-2.5 h to obtain a co-catalyst after molybdenum etching of CNT / Co-ZIF, namely CNT / CoMo-LDH; (8) Disperse 0.02-0.03 g CNT / CoMo-LDH in 30 mL water, add 0.30-0.40 g cadmium source, stir for 20-40 min, then add 0.12-0.15 g sulfur source and 0.3-0.5 mL NaOH (4M) solution, stir for 50-70 min, and perform hydrothermal reaction at 180-200 °C for 10-14 h to obtain CNT / CoMo-LDH / CdS composite photocatalyst.

[0010] The present invention provides the use of the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst CNT / CoMo-LDH / CdS in photocatalytic decomposition of water to produce hydrogen. Using a 300 W xenon lamp (with a 400 nm filter) as a light source, only 0.015 g of the composite photocatalyst and 80-120 mL of a 5%-10% volume fraction of lactic acid solution are required in the reaction system to achieve 40.91-46.76 mmol g -1 h -1 of hydrogen evolution efficiency.

[0011] Beneficial effects of the present invention: (1) The present invention utilizes the carboxyl groups on the surface of acid-functionalized carbon nanotubes to attract metal ions in ZIF through electrostatic action, thereby anchoring Co-ZIF on the carbon nanotubes; during the etching process, ion exchange and hydration reactions are used to make the surface of CNT / Co-ZIF rough and produce a layered structure, so that Co-ZIF is converted into CoMo-LDH, and finally CNT / CoMo-LDH is obtained; the co-catalyst obtained by this method, namely CNT / CoMo-LDH, after being composited with CdS, not only has good morphology and dispersion, but also the carbon nanotubes in series accelerate electron transfer, improve the separation and migration efficiency of photogenerated electrons and holes, thereby improving the photocatalytic water decomposition and hydrogen evolution performance of the nano-semiconductor CdS; (2) Compared with the prior art, the present invention has the following significant advantages: a hollow cage-like CoMo-LDH with a roughly dodecahedral skeleton structure is prepared by etching the rhombic dodecahedron-shaped Co-ZIF with metal salts. In terms of morphology, it can effectively avoid the disadvantage of easy aggregation and stacking of layered double hydroxides, has a large specific surface area, fully exposes more active sites, is conducive to electron transfer, and improves the separation and migration efficiency of photogenerated electrons and holes; in terms of energy band structure, its energy band structure can be regulated so that it has a higher barrier difference with CdS, and a heterojunction is constructed with CdS to promote electron transfer; ultimately, the hydrogen production rate of the composite photocatalyst is as high as 46.76 mmol g –1 h –1 , which is 11 times the hydrogen production rate of pure CdS; In order to illustrate the structure and photocatalytic water decomposition and hydrogen evolution performance of the composite photocatalyst of carbon nanotube-loaded layered double metal hydroxide and CdS prepared in the present invention, further description is given in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 FT-IR spectra of CNT, CNT / Co-ZIF, Co-ZIF and CNT / CoMo-LDH samples in Example 1; Figure 2 XRD spectra of CNT, CNT / Co-ZIF, CNT / CoMo-LDH and CNT / CoMo-LDH CdS samples in Example 1; Figure 3 The SEM image of the CNT / Co-ZIF sample prepared in Example 1; Figures a and b represent SEM images at different magnifications, respectively; Figure 4 The SEM image of the CNT / CoMo-LDH sample prepared in Example 1; Figures a and b represent SEM images at different magnifications, respectively; Figure 5 The SEM image of the CNT / CoMo-LDH / CdS sample prepared in Example 1; Figures a and b represent SEM images at different magnifications, respectively; Figure 6 This is a comparison chart of the photocatalytic hydrogen production performance of Examples 1 to 5; Figure 7 It is a comparison chart of the photocatalytic hydrogen production performance of Example 1 and Comparative Examples 1-5. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0014] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0015] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.

[0016] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.

[0017] The following example illustrates the preparation method of the composite photocatalyst of carbon nanotube-loaded layered double metal hydroxide and CdS (ie, carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst). Example 1

[0018] 0.016 g of acid-functionalized carbon nanotubes were dissolved in 20 mL of anhydrous methanol, 0.39 g of cobalt nitrate hexahydrate was added, and a uniform solution A was formed after ultrasonication at a frequency of 40 kHz for 1 min. 0.89 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and a uniform dispersion was obtained after ultrasonication at a frequency of 40 kHz for 1 min, which was marked as solution B. Solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor CNT / Co-ZIF.

[0019] 0.03 g of the precursor CNT / Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution C; 0.006 g of sodium molybdate dihydrate was dispersed in 10 mL of water, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CNT / CoMo-LDH co-catalyst was obtained after washing and drying.

[0020] Weigh 0.02 g of CNT / CoMo-LDH, ultrasonically disperse it in 30 mL of water, add 0.32 g of cadmium acetate dihydrate, stir for 20 min, then add 0.13 g of thioacetamide and 0.4 mL of NaOH (4M), continue stirring for 60 min, transfer the mixed solution to a 50 mL high-pressure reactor, hydroheat it at 180 °C for 12 h, wash and dry to obtain the composite photocatalyst CNT / CoMo-LDH / CdS.

[0021] The method for evaluating the photocatalytic hydrogen production performance of the obtained composite photocatalyst CNT / CoMo-LDH / CdS is as follows: The evaluation was conducted using a top-illuminated Pyrex glass reactor. Weigh 0.015 g of the prepared photocatalyst, disperse it in 100 mL of lactic acid solution (10 vol.%), place it in the reactor, connect the reaction device, keep the temperature of the reaction system at 6 °C, and use a 300 W xenon lamp (with a 400 nm filter) as the light source under magnetic stirring to evaluate the performance of photocatalytic decomposition of water to produce hydrogen. Before starting the reaction, evacuate the reaction system for 30 min to completely remove the air in the system. The amount of hydrogen produced by the reaction was quantitatively analyzed using a gas chromatograph equipped with a thermal conductivity detector.

[0022] After testing the photocatalytic hydrogen production of Example 1, the hydrogen production rate of the composite photocatalyst was 46.76 mmolg -1 h -1 .See Figure 6 shown.

[0023] Figure 1 From the FT-IR spectra of CNT / Co-ZIF and CNT / CoMo-LDH prepared in Example 1, it can be seen that CNT / Co-ZIF adds the characteristic peaks of pure Co-ZIF on the basis of CNT, which proves that Co-ZIF has successfully grown on CNT, and from the FT-IR spectrum of CNT / CoMo-LDH, it can be observed that compared with CNT / Co-ZIF, the characteristic peaks of Co-ZIF disappear, confirming that the ZIF structure has been successfully etched and destroyed using sodium molybdate.

[0024] Figure 2 The XRD spectra of CNT / Co-ZIF, CNT / CoMo-LDH and CNT / CoMo-LDH / CdS prepared in Example 1. The characteristic peaks of CNT / Co-ZIF cannot be observed in the XRD spectrum of CNT / CoMo-LDH because Mo 2+The Co-ZIF structure on CNT / Co-ZIF was completely etched and destroyed to obtain CNT / CoMo-LDH, so only the characteristic peak of LDH was observed. The characteristic peak of LDH was not observed on CNT / CoMo-LDH / CdS because the CdS loading on the outer layer was larger and the peak was stronger than that of CoMo-LDH, so only the characteristic peak of CdS was shown in XRD.

[0025] Figures 3-5 The SEM images of CNT / Co-ZIF, CNT / CoMo-LDH and CNT / CoMo-LDH / CdS prepared in Example 1. Figure 3 ) can be seen that CNTs are either entangled or interlaced on Co-ZIF, and it is not just a simple physical mixture. In the SEM image of CNT / CoMo-LDH ( Figure 4 ) shows that the octahedral ZIF structure in the precursor is destroyed, resulting in a disordered layer structure, and CNTs can still be observed interspersed in it. Through the SEM image of CNT / CoMo-LDH / CdS ( Figure 5 ) It can be seen that irregular CdS nanoparticles are completely coated on CNT / CoMo-LDH. The three sets of SEM images confirm the successful preparation of CNT / Co-ZIF, CNT / CoMo-LDH and CNT / CoMo-LDH / CdS. Example 2

[0026] 0.012 g of acid-treated carbon nanotubes were dissolved in 20 mL of anhydrous methanol, 0.34 g of cobalt nitrate hexahydrate was added, and a uniform solution A was formed after ultrasonication at a frequency of 40 kHz for 1 min. 0.85 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and a uniform dispersion was obtained after ultrasonication at a frequency of 40 kHz for 1 min, which was marked as solution B. Solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor CNT / Co-ZIF.

[0027] 0.03 g of the precursor CNT / Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution C; 0.03 g of sodium molybdate dihydrate was dispersed in 10 mL of water, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CNT / CoMo-LDH co-catalyst was obtained after washing and drying.

[0028] 0.022 g of CNT / CoMo-LDH was weighed and ultrasonically dispersed in 30 mL of water. 0.37 g of cadmium acetate dihydrate was added and stirred for 20 min. Then, 0.15 g of thioacetamide and 0.4 mL of NaOH (4 M) were added. After stirring for 60 min, the mixed solution was transferred to a 50 mL high-pressure reactor and hydrothermally heated at 190 °C for 10 h. After washing and drying, the composite photocatalyst CNT / CoMo-LDH / CdS was obtained.

[0029] After the photocatalytic hydrogen production test of Example 2, the hydrogen production rate of the composite photocatalyst was 40.91 mmolg -1 h -1 .See Figure 6 shown. Example 3

[0030] 0.018 g of acid-functionalized carbon nanotubes were dissolved in 20 mL of anhydrous methanol, 0.4 g of cobalt nitrate hexahydrate was added, and a uniform solution A was formed after ultrasonication at a frequency of 40 kHz for 1 min. 1.0 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and a uniform dispersion was obtained after ultrasonication at a frequency of 40 kHz for 1 min, which was marked as solution B. Solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor CNT / Co-ZIF.

[0031] 0.035 g of the precursor CNT / Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution C; 0.055 g of sodium molybdate dihydrate was dispersed in 10 mL of water, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CNT / CoMo-LDH co-catalyst was obtained after washing and drying.

[0032] Weigh 0.025 g of CNT / CoMo-LDH, ultrasonically disperse it in 30 mL of water, add 0.3 g of cadmium acetate dihydrate, stir for 20 min, then add 0.12 g of thioacetamide and 0.3 mL of NaOH (4M), continue stirring for 50 min, transfer the mixed solution to a 50 mL high-pressure reactor, hydroheat it at 180 °C for 14 h, wash and dry to obtain the composite photocatalyst CNT / CoMo-LDH / CdS.

[0033] After testing the photocatalytic hydrogen production of Example 3, the hydrogen production rate of the composite photocatalyst was 38.05 mmol / g. -1 h -1 .See Figure 6 shown. Example 4

[0034] 0.01 g of acid-functionalized carbon nanotubes was dissolved in 20 mL of anhydrous methanol, 0.32 g of cobalt chloride hexahydrate was added, and a uniform solution A was formed after ultrasonication at a frequency of 40 kHz for 1 min. 0.86 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and a uniform dispersion was obtained after ultrasonication at a frequency of 40 kHz for 1 min, which was marked as solution B. Solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor CNT / Co-ZIF.

[0035] 0.025 g of the precursor CNT / Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution C; 0.006 g of sodium molybdate dihydrate was dispersed in 10 mL of water, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CNT / CoMo-LDH co-catalyst was obtained after washing and drying.

[0036] 0.03 g of CNT / CoMo-LDH was weighed and ultrasonically dispersed in 30 mL of water. 0.4 g of cadmium acetate dihydrate was added and stirred for 20 min. Then, 0.15 g of thioacetamide and 0.5 mL of NaOH (4 M) were added. After stirring for 70 min, the mixed solution was transferred to a 50 mL high-pressure reactor and hydrothermally heated at 200 °C for 10 h. The composite photocatalyst CNT / CoMo-LDH / CdS was obtained after washing and drying.

[0037] After testing the photocatalytic hydrogen production of Example 4, the hydrogen production rate of the composite photocatalyst was 35.47 mmolg -1 h -1 .See Figure 6 shown. Example 5

[0038] 0.02 g of acid-functionalized carbon nanotubes were dissolved in 20 mL of anhydrous methanol, 0.31 g of cobalt nitrate hexahydrate was added, and a uniform solution A was formed after ultrasonication at a frequency of 40 kHz for 1 min. 0.80 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and a uniform dispersion was obtained after ultrasonication at a frequency of 40 kHz for 1 min, which was marked as solution B. Solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor CNT / Co-ZIF.

[0039] 0.04 g of the precursor CNT / Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and was evenly dispersed after being ultrasonically treated with an ultrasonic instrument with an ultrasonic frequency of 40 kHz for 1 min to obtain solution C; 0.14 g of phosphomolybdic acid was dispersed in 10 mL of water, and was evenly dispersed after being ultrasonically treated with an ultrasonic instrument with an ultrasonic frequency of 40 kHz for 1 min to obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CNT / CoMo-LDH co-catalyst was obtained after washing and drying.

[0040] Weigh 0.025 g of CNT / CoMo-LDH, use an ultrasonic instrument with an ultrasonic frequency of 40 kHz for 1 min, then disperse it in 30 mL of water, add 0.30 g of cadmium acetate dihydrate, stir for 20 min, then add 0.12 g of thioacetamide and 0.36 mL of NaOH (4M), continue stirring for 50 min, transfer the mixed solution to a 50 mL high-pressure reactor, hydroheat it at 190 ° C for 12 h, wash and dry to obtain the composite photocatalyst CNT / CoMo-LDH / CdS.

[0041] After the photocatalytic hydrogen production test of Example 5, the hydrogen production rate of the composite photocatalyst was 30.77 mmolg -1 h -1 .See Figure 6 shown.

[0042] Comparative Example 1: Weigh 0.3198 g of cadmium acetate dihydrate, use an ultrasonic instrument with an ultrasonic frequency of 40 kHz to sonicate for 1 min, then disperse it in 30 mL of water and stir it for 20 min. Then, add 0.1262 g of thioacetamide and 0.4 mL of NaOH (4M). After stirring for 1 h, transfer the mixed solution to a 50 mL high-pressure reactor, hydroheat it at 180 ° C for 12 h, and wash and dry it to obtain the photocatalyst CdS.

[0043] The photocatalytic hydrogen production test of Comparative Example 1 showed that the hydrogen production rate of the composite photocatalyst was 4.17 mmol / g. -1 h -1 .

[0044] Comparative Example 2: 0.0162 g of acid-functionalized carbon nanotubes were weighed and dispersed in 30 mL of water after ultrasonication at a frequency of 40 kHz for 1 min. 0.3198 g of cadmium acetate dihydrate was added and stirred for 20 min. Then, 0.1262 g of thioacetamide and 0.4 mL of NaOH (4 M) were added. After stirring for 1 h, the mixed solution was transferred to a 50 mL high-pressure reactor and hydrothermally heated at 180 ° C for 12 h. The photocatalyst CNT / CdS was obtained after washing and drying.

[0045] The photocatalytic hydrogen production test of Comparative Example 2 showed that the hydrogen production rate of the composite photocatalyst was 5.43 mmol / g. -1 h -1 .

[0046] Comparative Example 3: 0.0162 g of acid-functionalized carbon nanotubes were dissolved in 20 mL of anhydrous methanol, 0.3930 g of cobalt nitrate hexahydrate was added, and a uniform solution A was formed after ultrasonication at a frequency of 40 kHz for 1 min. 0.8864 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and a uniform dispersion was obtained after ultrasonication at a frequency of 40 kHz for 1 min, which was marked as solution B. Solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor CNT / Co-ZIF.

[0047] 0.03 g of the precursor CNT / Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to uniformly disperse the solution to obtain solution C; 0.0060 g of sodium molybdate dihydrate was dispersed in 10 mL of water, and ultrasonically dispersed to uniformly obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CNT / CoMo-LDH photocatalyst was obtained after washing and drying.

[0048] The photocatalytic hydrogen production test of Comparative Example 3 showed that almost no hydrogen was produced, and the hydrogen production rate was 0 mmolg -1 h -1 It can be seen that the photocatalytic performance of CNT / CoMo-LDH is extremely weak. This is because although LDH is a semiconductor, its photocatalytic efficiency is generally low due to its poor visible light response ability.

[0049] Comparative Example 4: 0.3930 g of cobalt nitrate hexahydrate was dissolved in 20 mL of anhydrous methanol, and 0.3930 g of cobalt nitrate hexahydrate was added, and an ultrasonic instrument with an ultrasonic frequency of 40 kHz was used to ultrasonicate for 1 min to form a uniform solution A; 0.8864 g of 2-methylimidazole was dissolved in 20 mL of anhydrous methanol, and an ultrasonic instrument with an ultrasonic frequency of 40 kHz was used to ultrasonicate for 1 min to disperse evenly, marked as solution B; solution B was added to solution A, stirred for 2 h, and then washed and dried to obtain the precursor Co-ZIF.

[0050] 0.03 g of the precursor Co-ZIF was dispersed in 20 mL of anhydrous ethanol, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution C; 0.0060 g of sodium molybdate dihydrate was dispersed in 10 mL of water, and was evenly dispersed after being ultrasonicated for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz to obtain solution D; solution D was poured into C, hydroheated at 90°C for 2 h, and the product CoMo-LDH co-catalyst was obtained after washing and drying.

[0051] 0.02 g of CoMo-LDH was weighed and ultrasonically dispersed in 30 mL of water. 0.3198 g of cadmium acetate dihydrate was added and stirred for 20 min. Then, 0.1262 g of thioacetamide and 0.4 mL of NaOH (4 M) were added. After stirring for 1 h, the mixed solution was transferred to a 50 mL high-pressure reactor and hydrothermally heated at 180 °C for 12 h. The composite photocatalyst CoMo-LDH / CdS was obtained after washing and drying.

[0052] After the photocatalytic hydrogen production test of Comparative Example 4, the hydrogen production rate of the composite photocatalyst was 30.45 mmolg -1 h -1 . The reason why the hydrogen production rates of the composite photocatalyst CoMo-LDH / CdS in Comparative Example 4 and the composite photocatalyst CNT / CoMo-LDH / CdS in Example 5 are similar is that, although carbon nanotubes are composited in Example 5, the molybdenum source is changed from sodium molybdate dihydrate to phosphomolybdic acid. Compared with the two, CoMo-LDH prepared by sodium molybdate dihydrate has better hydrogen evolution performance. When the raw material selection and its feeding ratio are unified, it can be concluded by comparing Example 1 and Comparative Example 4 that the addition of carbon nanotubes in the composite photocatalyst of the present invention can significantly improve the hydrogen evolution performance of the composite photocatalyst.

[0053] Comparative Example 5: 0.0162 g of acid-functionalized carbon nanotubes were dissolved in 35 mL of water, and 0.3930 g of cobalt nitrate hexahydrate, 0.0060 g of sodium molybdate dihydrate, and 0.2650 g of hexamethylenetetramine were added. Ultrasonication was performed for 1 min using an ultrasonic instrument with an ultrasonic frequency of 40 kHz, and then the mixture was uniformly dispersed and hydrothermally reacted at 90°C for 6 h. CNT / CoMo-LDH (nanosheets) were obtained.

[0054] Weigh 0.02 g of CNT / CoMo-LDH (nanosheets), use an ultrasonic instrument with an ultrasonic frequency of 40 kHz to sonicate for 1 min, then disperse it in 30 mL of water, add 0.3198 g of cadmium acetate dihydrate, stir for 20 min, then add 0.1262 g of thioacetamide and 0.4 mL of NaOH (4M), continue stirring for 1 h, transfer the mixed solution to a 50 mL high-pressure reactor, hydroheat it at 180 ° C for 12 h, wash and dry it to obtain the composite photocatalyst CNT / CoMo-LDH (nanosheets) / CdS.

[0055] The photocatalytic hydrogen production test of Comparative Example 5 showed that the hydrogen production rate of the composite photocatalyst was 38.27 mmol / g. -1 h -1 . The reason why the photocatalytic hydrogen evolution performance of comparative example 5 is better than that of embodiments 3, 4, and 5 is that the optimal raw materials and their proportions are selected in the preparation process of comparative example 5. If the raw materials and their proportions are unified, and only the preparation methods are compared, the photocatalytic hydrogen evolution performance of the photocatalyst of embodiment 1 of the present invention is still higher than that of comparative example 5. This is because the CoMo-LDH prepared in comparative example 5 is a block structure formed by the accumulation of nanosheets. Compared with the CoMo-LDH nanocage structure prepared in embodiment 1, the contact area between LDH and CdS in comparative example 5 is smaller, so the heterogeneous interfaces constructed are also less, resulting in lower photocatalytic hydrogen evolution performance of comparative example 5.

[0056] The photocatalytic hydrogen production performance of the composite photocatalyst CNT / CoMo-LDH / CdS prepared by the present invention was evaluated. Figure 6 In order to verify the implementation effect of the present invention, the effect data of the comparative examples 1 to 5 provided above are shown in Figure 7 shown.

[0057] The photocatalytic hydrogen production test was carried out on Examples 1 to 5 respectively. Figure 6As shown in the figure, it can be seen that the photocatalytic hydrogen production rates of CNT / CoMo-LDH / CdS composite photocatalysts prepared from different raw material sources vary greatly. Using the raw materials and method of Example 1, a composite photocatalyst CNT / CoMo-LDH / CdS with the best photocatalytic water decomposition hydrogen production performance can be prepared, and its photocatalytic hydrogen production rate is as high as 46.76 mmol g –1 h –1 The photocatalytic hydrogen production rates of pure CdS in Comparative Example 1, CNT / CdS in Comparative Example 2, CNT / CoMo-LDH in Comparative Example 3, CoMo-LDH / CdS in Comparative Example 4, and CNT / CoMo-LDH (nanosheet) / CdS synthesized by ordinary hydrothermal method in Comparative Example 5 were 4.17, 5.43, 0, 30.45, and 38.27 mmol g, respectively. –1 h –1 ( Figure 7 ) (wherein Comparative Example 5 selects the best raw materials and their ratios during the preparation process, so the hydrogen evolution performance of Comparative Example 5 is higher than that of Example 4 and Example 5), which illustrates that the composite photocatalyst CNT / CoMo-LDH / CdS constructed by etching Co-ZIF on CNT to CoMo-LDH in the present invention has excellent performance of photocatalytic water decomposition and hydrogen production, and the constructed CoMo-LDH / CdS heterojunction is more conducive to the transfer of photogenerated electrons, thereby facilitating the migration and transmission of electrons and holes, inhibiting the recombination of photogenerated carriers, and ultimately improving the hydrogen evolution efficiency of photocatalytic water decomposition.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst, characterized in that: The mass fractions of carbon nanotubes, layered double hydroxides and cadmium sulfide in the composite photocatalyst are 0.02%-0.04%, 46.96%-51.98% and 48%-53%, respectively.

2. A method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 1, characterized in that The following steps are involved: In the first step, the carbon nanotubes loaded with highly dispersed Co-ZIF are etched by molybdenum source through ion exchange and hydration reaction, so that the Co-ZIF on CNT / Co-ZIF evolves into a layered structure CoMo-LDH to obtain CNT / CoMo-LDH; In the second step, CNT / CoMo-LDH was used as a carrier, and a cadmium source, a sulfur source and a sodium hydroxide solution were added to hydrothermally load CdS in situ to obtain a CNT / CoMo-LDH / CdS composite photocatalyst. Through reasonable design, CNTs were interspersed in the composite material to accelerate the electron transfer in the composite material. CoMo-LDH was introduced into the composite material to construct a heterostructure with CdS.

3. The method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 2, characterized in that The specific steps are as follows: (1) Disperse 1 g of carbon nanotubes in 100 mL of a mixed acid of sulfuric acid and nitric acid in a volume ratio of 3:1, treat with ultrasound for 5 min, and reflux in a 60°C water bath for 5 h; after the reaction is completed and cooled to room temperature, wash the reactant with water and filter it until the pH is neutral, and freeze-dry to obtain acid-treated carbon nanotubes (CNT); (2) Dissolve 0.01-0.02 g of acid-treated carbon nanotubes in 20 mL of anhydrous methanol or water, add 0.31-0.40 g of cobalt source, and sonicate for 1 min to form a uniform solution A; (3) Dissolve 0.8-1.0 g of 2-methylimidazole in 20 mL of anhydrous methanol or water and sonicate for 1 min to form a uniform solution B; (4) The solution A in step (2) and the solution B in step (3) are mixed evenly and stirred for 2 h to obtain a composite CNT / Co-ZIF in which Co-ZIF is connected in series by carbon nanotubes; (5) Disperse 0.02-0.04 g of the CNT / Co-ZIF obtained in step (4) in 40 mL of anhydrous ethanol and sonicate for 1 min to form a uniform solution C; (6) Dissolve 0.006-0.14 g of molybdenum source in 10 mL of water and sonicate for 1 min to form a uniform solution D; (7) The solution C in step (5) and the solution D in step (6) are mixed evenly, and hydrothermal treatment is performed at 80-100° C. for 1.5-2.5 h to obtain a catalyst CNT / CoMo-LDH after molybdenum etching of CNT / Co-ZIF; (8) Disperse 0.02-0.03 g CNT / CoMo-LDH in 30 mL water, add 0.30-0.40 g cadmium source, stir for 20-40 min, then add 0.12-0.15 g sulfur source and 0.3-0.5 mL NaOH solution, stir for 50-70 min, and perform hydrothermal reaction at 180-200 °C for 10-14 h to obtain CNT / CoMo-LDH / CdS composite photocatalyst.

4. The method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 3, characterized in that: The cobalt source is any one of cobalt nitrate and cobalt chloride; the molybdenum source is Keggin type phosphomolybdic acid PMo 12 , ammonium molybdate AMT, sodium molybdate; the cadmium source is any one of cadmium chloride, cadmium nitrate, cadmium acetate; the sulfur source is any one of thiourea, sodium sulfide, thioacetamide.

5. The method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 3, characterized in that: The solvent used in steps (2) and (3) is the same.

6. The method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 3, characterized in that: The concentration of the NaOH solution in step (8) is 4M.

7. The method for preparing the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 3, characterized in that: During the ultrasonic process of steps (1) to (6), the ultrasonic frequency was set to 40 kHz.

8. Use of the carbon nanotube / layered double metal hydroxide / cadmium sulfide composite photocatalyst according to claim 1 in photocatalytic water decomposition to produce hydrogen.

9. The use according to claim 8, characterized in that: Using a 300 W xenon lamp light source with a 400 nm filter, 0.015 g of composite photocatalyst and 80-120 mL of 5%-10% lactic acid solution in the reaction system, the hydrogen evolution efficiency can reach 40.91-46.76 mmol g -1 h -1 .

Citation Information

Cited By

  • Preparation method of porous hollow sphere cadmium sulfide / nickel-aluminum hydrotalcite / flower-like carbon nitride composite photocatalyst

    CN122682626A